Social media maintenance expectations and relationship satisfaction among firs-year psychology students at the University of Limpopo : attachment styles as a mediating factor - Nethate, Grace (My University, 2025)
This study investigated the relationship between Social Media Maintenance Expectations (SMME), Relationship Satisfaction (RS), and Attachment Styles among first-year Psychology students at the University of Limpopo. The research aimed to understand the mediating role of attachment styles and explore the factors influencing RS within the context of social media use. The data were collected through surveys and analysed using mediation analysis and ordinal regression models. The findings revealed several important insights. First, higher attachment styles were positively associated with increased RS (P Za = 0.002 < 0.05), even when controlling for SMME. This highlights the significance of attachment orientations in predicting RS among first-year Psychology students. Second, individuals with anxious attachment styles tended to have higher expectations for social media maintenance. This suggests that attachment styles influence individuals' perceptions of how relationships should be maintained on social media platforms. Furthermore, SMME played a significant role in influencing RS, independently of the mediating effect of attachment styles. The more an individual’s SMME were met, the higher their RS. These findings highlight the importance of considering attachment styles and SMME in understanding relationship dynamics and developing interventions to promote healthy and satisfying relationships among first-year Psychology students. Recommendations include attachment-aware relationship interventions, education on healthy social media use, support for relationship building, continued research and evaluation, and promoting relationship quality awareness. By implementing these recommendations, educational institutions and counselling centres can provide effective interventions and support systems to enhance relationship quality and well-being among first-year university students.
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2025
Keywords: Social media maintenance; Relationship satisfaction; Attachment styles; Fist year psychology students; Communication and technology; Parasocial relationships; Social media; Attachment behavior; College students -- South Africa -- Limpopo